2021
DOI: 10.3389/fmed.2021.694385
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy and Safety of Enhanced Recovery After Surgery for Cesarean Section: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Observational Studies

Abstract: Background: Enhanced recovery after surgery (ERAS) has been adopted in some maternity units and studied extensively in cesarean section (CS) in the last years, showing encouraging results in clinic practice. However, the present evidence assessing the effectiveness of ERAS for CS remains weak, and there is a paucity in the published literature, especially in improving maternal outcomes. Our study aimed to systematically evaluate the clinical efficacy and safety of ERAS protocols for CS.Methods: A systematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 57 publications
2
24
1
Order By: Relevance
“…In addition, there is also evidence to suggest that discharge the first day or two appears to be safe and acceptable in low-risk patients undergoing cesarean delivery. In the future, ongoing evaluation of maternal outcomes, and neonatal factors [20].…”
Section: Eracsmentioning
confidence: 99%
“…In addition, there is also evidence to suggest that discharge the first day or two appears to be safe and acceptable in low-risk patients undergoing cesarean delivery. In the future, ongoing evaluation of maternal outcomes, and neonatal factors [20].…”
Section: Eracsmentioning
confidence: 99%
“…Three studies 14 , 15 , 19 from the Sultan et al meta-analytic study were not included, and an RCT published in Chinese (without a full English translation), involving 572 women, was added. 24 Meng at al 46 also found that the primary outcome of LOS was reduced with ERAC and that secondary outcomes (complication rates, pain scores, opioid consumption, and hospitalization costs) were improved with ERAC. There were no differences in maternal readmission rates.…”
Section: Introductionmentioning
confidence: 98%
“…There have since been 11 new peer-reviewed ERAC studies published that fulfill the same inclusion criteria as Sultan et al, 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 and 2 published meta-analyses comparing ERAC with standard care. 33 , 46 In the 22 ERAC implementation studies published to date, the outcomes described are wide-ranging and heterogeneous ( Table 1 ). Of these studies, 4 are randomized controlled trials (RCTs) 13 , 20 , 23 , 24 and 2 are multicenter studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more interest is growing to achieve better perioperative management and outcome of CS in form of enhanced recovery after surgery (ERAS) concept [2]. Effective analgesia allows early mobilization, increases breastfeeding success, and fast recovery; it reduces hospital stay, costs and indeed a comfort to surgeons and increases the overall patient satisfaction [3,4]. Systemic opioid is commonly used as one of the pain control approaches, however, there are side effects such as pruritus, nausea, and vomiting.5 Peripheral nerve blocks have become vital for multimodal opioid-sparing analgesia in a multitude of surgical procedures.…”
Section: Introductionmentioning
confidence: 99%